Dog Man - Pilkey, Dav, 1966- (New York, NY : Graphix, an imprint of Scholastic, 2016)
Dog Man, a crimefighter with the head of a police dog and the body of a policeman, faces off against his archnemesis Petey the Cat.
"Tree House Comix Proudly Presents"
Keywords: Graphic novels; Dogs -- Fiction; Police -- Fiction; Cats -- Fiction; Humorous stories; Graphic novels